Neurotropic growth factors and glycosaminoglycan based matrices to induce dopaminergic tissue formation. (October 2015) - Schurig, Katja; Zieris, Andrea; Hermann, Andreas; Freudenberg, Uwe; Heidel, Sabine; Grimmer, Milauscha; Storch, Alexander; Werner, Carsten
Abstract: Current cell replacement therapies in Parkinson's disease (PD) are limited by low survival of transplanted cell and lacking regeneration of neuronal circuitries. Therefore, bioartificial cell carriers and growth/differentiation factors are applied to improve the integration of transplants and maximize newly generated and/or residual dopaminergic function. In this work, biohybrid poly(ethylene glycol) (starPEG)-heparin hydrogels releasing fibroblast growth factor 2 (FGF-2) and glial-derived neurotrophic factor (GDNF) were used to trigger dopaminergic tissue formation by primary murine midbrain cells in vitro . Matrix-delivered FGF-2 enhanced cell viability while release of GDNF had a pro-neuronal/dopaminergic effect. Combined delivery of both factors from the glycosaminoglycan-based matrices resulted in a tremendous improvement in survival and maturation capacity of dopaminergic neurons as obvious from tyrosine hydroxylase expression and neurite outgrowth. The reported data demonstrate that glycosaminoglycan-based hydrogels can facilitate the administration of neurotrophic factors and are therefore instrumental in potential future treatments of PD.